An introduction to early Judaism - VanderKam, James C. 1946- (William B. Eerdmans Publishing Company, 2022)
Based on the best archaeological research, this volume explores the history of Judaism during the Second Temple period (516 BCE-70 CE), describing the body of Jewish literature written during these centuries and the most important groups, institutions, and practices of the time. Particularly interesting are VanderKam's depiction of events associated with Masada and, more briefly, the Bar Kokhba revolt--as well as his commentary on texts unearthed in places like Elephantine and Qumran. Now in its second edition, with additional material and updated throughout, this book remains the preeminent guide to early Judaism for anyone looking for a text that is concise and accessible while still comprehensive--and written by one of the foremost experts in the field
Keywords: Frühjudentum; Jews / History / 586 B.C.-70 A.D.; Judaism / History / Post-exilic period, 586 B.C.-210 A.D.; Bible / Apocrypha / Criticism, interpretation, etc; Apocryphal books (Old Testament) / Criticism, interpretation, etc; Bible / Apocrypha; Apocryphal books (Old Testament); Jews; Judaism / Post-exilic period (Judaism); 586 B.C.-210 A.D.; Criticism, interpretation, etc; History